The Interrelationships Between U.S. and Foreign Equity Market Yields: Tests of Granger Causality - Cochran, Steven J.; Mansur, Iqbal (Journal of International Business Studies, 1991)
This study examines the interrelationships between yields on the U.S. and several foreign market portfolios over the 1980–89 period. Tests of Granger causality are used to investigate the effects of uni-directional causality, bi-directional causality, and contemporaneous adjustment in the determination of market rates of return. The results indicate that international equity market returns are largely contemporaneously determined, and the significance of contemporaneous effects varied over time. Uni-directional and bi-directional causality were found to be relatively weak.